Inibidores de proteases cisteínicas de raízes de Crotalaria pallida: isolamento, purificação caracterização e avaliação de sua ação contra Meloidogyne incognata - Andrade, Lúcia Betânia da Silva (2008)
Nematodes of the genus Meloidogyne are among the most damaging nematodes in agriculture, causing annual losses estimated at 100 million dollars worldwide. Plants of the genus Crotalaria, efficient as traps in the control of nematodes, are used for decades by small farmers [...]